2023
DOI: 10.1093/ofid/ofad143
|View full text |Cite
|
Sign up to set email alerts
|

Early Target Attainment With Continuous Infusion Meropenem and Piperacillin/Tazobactam and Utilization of Therapeutic Drug Monitoring in Critically Ill Patients: A Retrospective Cohort Study From 2017 to 2020

Abstract: Objectives We analyzed the attainment of early pharmacological targets of continuous infusion meropenem and piperacillin/tazobactam and the use and effect of a real-time TDM program on subsequent dosing and target attainment in critically ill patients. Methods This was a single centre, retrospective study among patients hospitalized in the intensive care unit in a Swiss tertiary care hospital from 2017 to 2020. The primary ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 47 publications
0
2
0
Order By: Relevance
“…In this scenario, adopting altered dosing strategies based on CI administration and implementing a therapeutic drug monitoring (TDM)-guided approach may significantly increase the likelihood of attaining aggressive PK/PD targets in critically ill patients (Guilhaumou et al, 2019). Specifically, the proportion of critical patients failing in attaining aggressive PK/PD targets with CI beta-lactams ranged from 5% to 28% (Richter et al, 2019;Chiriac et al, 2021;Gatti et al, 2022;Hagel et al, 2022;Dräger et al, 2023). A previous retrospective study including 166 critically ill patients (6.6% OLT recipients) reported a proportion of failure in attaining aggressive PK/PD targets at first TDM assessment with CI piperacillintazobactam and meropenem of 4.9% and 13.5%, respectively (Gatti et al, 2022).…”
Section: Optimal Pk/pd Target Attainment For Beta-lactamsmentioning
confidence: 99%
“…In this scenario, adopting altered dosing strategies based on CI administration and implementing a therapeutic drug monitoring (TDM)-guided approach may significantly increase the likelihood of attaining aggressive PK/PD targets in critically ill patients (Guilhaumou et al, 2019). Specifically, the proportion of critical patients failing in attaining aggressive PK/PD targets with CI beta-lactams ranged from 5% to 28% (Richter et al, 2019;Chiriac et al, 2021;Gatti et al, 2022;Hagel et al, 2022;Dräger et al, 2023). A previous retrospective study including 166 critically ill patients (6.6% OLT recipients) reported a proportion of failure in attaining aggressive PK/PD targets at first TDM assessment with CI piperacillintazobactam and meropenem of 4.9% and 13.5%, respectively (Gatti et al, 2022).…”
Section: Optimal Pk/pd Target Attainment For Beta-lactamsmentioning
confidence: 99%
“…Several clinical studies showed that attaining an aggressive pharmacokinetic/ pharmacodynamic (PK/PD) target of 100%f T >4-8 × MIC with continuous infusion (CI) betalactams among critically ill patients was associated with both the maximization of clinical efficacy and the suppression of resistance development [13][14][15][16][17][18][19][20]. Failure in early attainment of this aggressive PK/PD target of piperacillin-tazobactam was shown to be as high as 80% during intermittent or extended infusion administration [21], and around 5-28% during CI administration [22][23][24][25][26]. All studies assessing aggressive PK/PD target attainment of piperacillin-tazobactam were based solely on piperacillin concentrations, without taking tazobactam exposure into account.…”
Section: Introductionmentioning
confidence: 99%